Rola nowych mediów w relacjonowaniu wydarzeń w sytuacji kryzysowej. Wybrane zagadnienia. - Łokić, Paweł (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
Article take selected issues concerning coverage of events of a crisis through the mass media. It has been discussed phenomenon of the impact of media on government policy towards crises and security risks . In the following study refers to the positive and negative aspects of the relationship between crisis and the new media. Article discusses the risks related with use of the Internet by terrorist organizations and problem of verification of User-Generated Content in the traditional mass media organizations . The article also focuses on the positive aspects of the use of new media in crisis. The conclusion of the study is bipolarity of the impact of mass media on crisis and security threat.